Phase 1 Study of Safety, Tolerability, and Pharmacokinetics of PTC299, an Inhibitor of Stress‐Regulated Protein Translation. Issue 4 (2nd February 2016) - Weetall, Marla; Davis, Thomas; Elfring, Gary; Northcutt, Valerie; Cao, Liangxian; Moon, Young‐Choon; Riebling, Peter; Dali, Mandar; Hirawat, Samit; Babiak, John; Colacino, Joseph; Almstead, Neil; et al.
Abstract: PTC299 is a novel small molecule that specifically blocks the production of protein from selected mRNAs that under certain conditions use noncanonical ribosomal translational pathways. Hypoxia, oncogenic transformation, and viral infections limit normal translation and turn on these noncanonical translation pathways that are sensitive to PTC299. Vascular endothelial cell growth factor (VEGF) is an example of a transcript that is posttranscriptionally regulated. Single doses of PTC299 (0.03 to 3 mg/kg) were administered orally to healthy volunteers in a phase 1 single ascending‐dose study. In a subsequent multiple ascending‐dose study in healthy volunteers, multiple‐dose regimens (0.3 to 1.2 mg/kg twice a day or 1.6 mg/kg 3 times a day for 7 days) were evaluated. PTC299 was well tolerated in these studies. As expected in healthy volunteers, mean plasma VEGF levels did not change. Increases in Cmax and AUC of PTC299 were dose‐proportional. The target trough plasma concentration associated with preclinical efficacy was achieved within 7 days at doses of 0.6 mg/kg twice daily and above. These data demonstrate that PTC299 is orally bioavailable and well tolerated and support clinical evaluation of PTC299 in cancer, certain viral infections, or other diseases in which deregulation of translational control is a causal factor.